"Online Exit Exam Preparation" Strategically facing a Nursing Competency Test during the COVID-19 Pandemic - Maria Imaculata Ose; Sulidah Sulidah; Dewy Haryanti Parman (Babali Nursing Research, 2021)
Introduction: The enactment of Law Number 2 of 2020 from the Ministry of Education and Culture of the Republic of Indonesia concerning The Graduation Exam System for Health Graduates has a significant impact on universities, affecting the number of students who can graduate. Looking at the description of these problems, it is necessary to develop a strategy in dealing with the "Exit Exam" competency test for students majoring in the health science faculty of nursing, namely "Preparation for Exit Exam Online," so that they can answer these problems. Methods: This research method uses one group pretest-posttest design with a sample size of 54 people. Results: The results showed increased the tryout value that after participating in online tutoring activities in facing competency tests. Conclusion: This online guidance is one of the strategies in dealing with competency tests during the Covid-19 pandemic in nursing students.